Characterizing Traffic-Related Ultrafine Particles in Roadside Microenvironments: Spatiotemporal Insights from Industrial Parks - Sultan F.I. Abdillah; Sheng-Jie You; Ya-Fen Wang (Aerosol and Air Quality Research)
Abstract Ultrafine particles (UFPs; PM0.1) and black carbon (BC) were measured at different roadside microenvironments in the vicinity of the urban industrial park area. Simultaneous measurement campaigns were conducted at industrial roadside (IN), residential roadside (RS), and urban background (UB) throughout different seasons. Spatiotemporal variability as well as correlations between pollutants and confounding factors (traffic profiles and meteorological conditions) were analyzed. The observed average roadside UFPs particle number concentration (UFPs PNC) and BC concentrations were in the order of IN (38,000 ± 9,000 # cm−3 and 2,500 ± 600 ng m−3) > RS (25,000 ± 8,000 # cm−3 and 1,900 ± 300 ng m−3) > UB (23,000 ± 9,000 # cm−3 and 1,400 ± 300 ng m−3). Furthermore, 11.26%–16.06% and 20.35%–24.32% increases of the average UFPs PNC and BC mass concentrations were identified during cold period at all measurement sites. Additionally, peak average concentrations of UFPs PNC and BC were identified at IN and RS during morning rush-hour and weekdays periods, following the diurnal profiles of traffic flux compositions and total vehicle number per day. Intra-urban spatial variability of UFPs was identified between roadsides and urban background (IQR/M ratio ≥ 2, ρ ≤ 0.05), highlighting the heterogeneity characteristic of the pollutant. Both pollutants at IN and RS were significantly influenced by traffic activities, while at UB, they were associated with meteorological conditions and secondary emission. Elevated levels of pollutants identified in this study have exceeded typical “high-level” UFPs according to WHO AQG 2021, indicating an intensified exposure risk for pedestrians and residents. This study serves as reference for future epidemiological study related to roadside UFPs in typical urban microenvironments such as industrial park areas.